Adaptive filtering fundamentals of least mean squares with MATLAB - Poularikas, Alexander D., 1933- (CRC Press, 2014)
Adaptive filters are used in many diverse applications, appearing in everything from military instruments to cellphones and home appliances. Adaptive Filtering: Fundamentals of Least Mean Squares with MATLAB® covers the core concepts of this important field, focusing on a vital part of the statistical signal processing area-the least mean square (LMS) adaptive filter.